Changes of oscillatory activity in pitch processing network and related tinnitus relief induced by acoustic CR neuromodulation - Adamchic, Ilya; Hauptmann, Christian; Tass, Peter (Frontiers in Systems Neuroscience, 2012)
Chronic subjective tinnitus is characterized by abnormal neuronal synchronization in the central auditory system. As shown in a controlled clinical trial, acoustic coordinated reset (CR) neuromodulation causes a significant relief of tinnitus symptoms along with a significant decrease of pathological oscillatory activity in a network comprising auditory and non-auditory brain areas, which is often accompanied with a significant tinnitus pitch change. Here, we studied if the tinnitus pitch change correlates with a reduction of tinnitus loudness and/or annoyance as assessed by visual analogue scale (VAS) scores. Furthermore, we studied if the changes of the pattern of brain synchrony in tinnitus patients induced by 12 weeks of CR-therapy depend on whether or not the patients undergo a pronounced tinnitus pitch change. For this, we applied standardized low-resolution brain electromagnetic tomography (sLORETA) to EEG recordings from two groups of patients with a sustained CR-induced relief of tinnitus symptoms with and without tinnitus pitch change. We found that absolute changes of VAS loudness and VAS annoyance scores significantly correlate with the modulus of the tinnitus pitch change. Moreover, as opposed to patients with weak or no pitch change we found a significantly stronger decrease in gamma power in patients with pronounced tinnitus pitch change in right parietal cortex (BA 1, 40), right frontal cortex (BA 8, 9, 46), and left frontal cortex (BA 4, 6), combined with a significantly stronger increase of alpha (10-12 Hz) activity in the right anterior cingulate cortex (BA 32, 24). In addition, we revealed a significantly lower functional connectivity in the gamma band between the right dorsolateral prefrontal cortex (BA 9) and the right anterior cingulate cortex (BA 32) after 12 weeks of CR-therapy in patients with pronounced pitch change. Our results indicate a substantial, CR-induced reduction of tinnitus-related auditory binding in a pitch processing network.